2015
DOI: 10.3747/pdi.2012.00224
|View full text |Cite
|
Sign up to set email alerts
|

Peginesatide to Manage Anemia in Chronic Kidney Disease Patients on Peritoneal Dialysis

Abstract: ♦ Background: Peginesatide is a novel, synthetic, peptidebased pegylated erythropoiesis-stimulating agent that is designed specifically to stimulate the erythropoietin receptor. The purpose of the present study was to assess, for the first time, the efficacy and safety of peginesatide in chronic kidney disease (CKD) patients receiving peritoneal dialysis (PD) and previously on epoetin treatment. ♦ Methods: In this open-label multicenter study, 59 PD patients with CKD were converted from epoetin (alfa or beta) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Hernández-Navarrete et al [ 12 ] observed stable hemoglobin levels at 24 months postransplant after pretransplant EPO and iron dextran administration with the use of an intraoperative cell saver in 3 kidney transplants patients. Zabaneh et al [ 13 ] reported that most peritoneal dialysis patients with chronic kidney disease maintained hemoglobin levels between 10 g/dL and 12 g/dL (63.0%) and within ±1.0 g/dL of the baseline level (60.9%) during the 25-week evaluation period. The mean hemoglobin value during the evaluation period was 11.3±1.07 g/dL and the mean change from baseline was 0.10±1.15 g/dL (95% confidence limit; -0.24–0.44 g/dL).…”
mentioning
confidence: 99%
“…Hernández-Navarrete et al [ 12 ] observed stable hemoglobin levels at 24 months postransplant after pretransplant EPO and iron dextran administration with the use of an intraoperative cell saver in 3 kidney transplants patients. Zabaneh et al [ 13 ] reported that most peritoneal dialysis patients with chronic kidney disease maintained hemoglobin levels between 10 g/dL and 12 g/dL (63.0%) and within ±1.0 g/dL of the baseline level (60.9%) during the 25-week evaluation period. The mean hemoglobin value during the evaluation period was 11.3±1.07 g/dL and the mean change from baseline was 0.10±1.15 g/dL (95% confidence limit; -0.24–0.44 g/dL).…”
mentioning
confidence: 99%